Recovery of Unaided Hearing After Cochlear Implantation in Patient With Bilateral Menière's Disease. Issue 8 (28th September 2022) - Raymond, Mallory; Strange, Christine; Rizk, Habib
Abstract : Objective: To report a novel occurrence of unaided hearing recovery after cochlear implantation in a patient with Menière's disease. Patients: A 49-year-old woman with bilateral Menière's disease and vestibular migraine. Intervention(s): Cochlear implantation Main Outcome Measure(s): Postoperative unaided and aided pure tone thresholds and speech recognition measures. Results: Six-month postoperative unaided hearing in the implanted ear was in the moderate sensorineural hearing loss range with a speech reception threshold of 45 dB and word recognition score of 95%, representing a significant improvement from preoperative hearing, which was in the profound sensorineural hearing loss range with an unaided speech awareness threshold of 75 dB and inability to perform speech recognition testing. Aided testing also demonstrated an expected postoperative improvement after 6 months with a CNC word and AzBio in quiet score of 96% and 93%, respectively, from 0% and 9% preoperatively. Conclusion: Unaided hearing improvement after cochlear implantation in a patient with Menière's disease is unexpected, but possible and might lend insight into the poorly understood underlying mechanisms of sensorineural hearing loss in patients with Menière's disease.